Numerical Solution of a Kind of Fractional Parabolic Equations via Two Difference Schemes - Abdon Atangana; Dumitru Baleanu (Abstract and Applied Analysis)
A kind of parabolic equation was extended to the concept of fractional calculus. The resulting equation is, however, difficult to handle analytically. Therefore, we presented the numerical solution via the explicit and the implicit schemes. We presented together the stability and convergence of this time-fractional parabolic equation with two difference schemes. The explicit and the implicit schemes in this case are stable under some conditions.